BEYOND MORAL COMPLIANCE: FAITH, TRUST, AND SOCIO-ECONOMIC BONDING IN INDONESIAN ISLAMIC MICROENTERPRISES - Mansur Mansur; Siti Nur Mahmudah; Fitria Nur Masithoh; Sahrul Sahrul (Universitas Nurul Jadid, 2026)
This article examines how faith-based ethical norms generate economic resilience through socio-economic bonding in Indonesian Islamic microenterprises. A qualitative case study was conducted on a traditional food enterprise in Sampang, East Java, operating continuously from 1995 to 2025. Data were collected through semi-structured interviews with eight participants (owner, family members, repeat and occasional customers), non-participant observation, and document analysis. Using reflexive thematic analysis and process tracing, the study identifies three interconnected mechanisms: faith-driven trust formation, ethical reciprocity, and community embeddedness. The findings demonstrate that repeated ethical conduct—pricing transparency, product consistency, and courteous service—accumulates into relational capital that stabilizes customer loyalty and generates word-of-mouth diffusion. This mechanism enhances enterprise resilience against external shocks such as seasonal fluctuations, though the single-case design limits generalizability. The study contributes to Islamic economics by conceptualizing ethical practice as a relational capital formation process, offering a grassroots perspective on microenterprise sustainability in Muslim-majority contexts.